MENINGKATKAN MOTIVASI BELAJAR PJOK MELALUI PEMBERIAN REWARD DAN PUNISHMENT PADA MATERI LARI MELEWATI RINTANGAN SISWA KELAS VIII SMPN 8 BANJARBARU - Setiawan, Muhammad; Arie Rakhman; Trinaldi Andika Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to enhance students' motivation in Physical Education, Sports, and Health (PJOK) by implementing reward and punishment strategies in the context of obstacle running for eighth-grade students at SMPN 8 Banjarbaru. This study was prompted by the insufficient motivation of pupils in PJOK education. Students often exhibit less activity, diminished confidence, and a lack of enthusiasm during learning practice tasks. Furthermore, student learning outcomes remain inadequate and have not reached the anticipated level of proficiency. The pre-cycle data indicated an average student score of 69, accompanied by a learning completion rate of merely 25%. This research employed the Classroom Action Research (CAR) methodology, executed in two cycles. Each cycle comprised preparation, execution, observation, and reflection. The research participants comprised 32 eighth-grade students from SMPN 8 Banjarbaru during the 2025/2026 academic year. Data gathering methods included observation, assessments of learning outcomes, surveys on learning motivation, and documentation. The research data were evaluated using both quantitative and qualitative descriptive methods. The findings indicated that the implementation of reward and punishment strategies enhanced student motivation and academic performance. In Cycle I, the mean student score rose to 76, accompanied by a completion rate of 63%. In cycle II, the mean score rose to 85, accompanied by a completion rate of 87.5%. Moreover, pupils exhibited increased activity, discipline, confidence, and enthusiasm throughout the learning process. The application of rewards and penalties effectively enhances motivation for learning Physical Education (PJOK) in the obstacle course curriculum for eighth-grade students at SMPN 8 Banjarbaru.